Hemodialysis Catheter Thrombi: Visualization and Quantification of Microstructures and Cellular Composition. Issue 3 (July 2013) - Lucas, Thabata C.; Tessarolo, Francesco; Veniero, Patrizia; Caola, Iole; Piccoli, Federico; Haase, Albrecht; Nollo, Giandomenico; Huebner, Rudolf; Brunori, Giuliano
Purpose: Despite the increasing use of central venous catheters (CVC) for hemodialysis in clinical practice, the role of CVC in thrombus development is poorly understood. This work aims at defining new methods and protocols for assessing the micromorphology and composition of thrombi formed into tunneled and non-tunneled hemodialysis CVC removed from patients. Methods: Twenty-nine CVCs were collected and the microscopic features of intra-luminal thrombi were quantified by scanning electron microscopy (SEM) and visualized by two photon laser scanning microscopy (TPLSM). Results: SEM quantification showed that fibrin was the most abundant structure in CVC thrombi. Specifically, the median micromorphologic composition of the surface layer resulted in: 42.6% of fibrin plaque, 16.3% of fibrin network, 0.4% of fibrin fibers, 9.3% of platelets, 10.3% of erythrocytes and 1.7% of white blood cells. TPLSM showed that sub-surface layers were instead composed by smaller amounts of fibrin and platelets and higher amounts of blood cells. Conclusions: Integration of SEM and TPLSM was found to be an excellent tool for characterizing thrombi in hemodialysis CVC removed from patients. Protocols and techniques presented here may be useful in the development and testing of new strategies for limiting thrombus formation on vascular access because of CVC.